Exploring the GHG mitigation potential in rice production - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
CCAFS webinar Exploring the GHG mitigation potential in rice production on 18 September 2014. Presenters: Dr Reiner Wassmann, IRRI and Dr Sultan Ahmed, Government of Bangladesh. Read more about the webinar and download related research materials. https://ccafs.cgiar.org/exploring-ghg-mitigation-potential-rice-production